Methods of modeling technological processes of construction of buildings and structures - BASARAB, Volodymyr (Ways to Improve Construction Efficiency, 2025)
The article is devoted to the study of methods for modeling technological processes of building and construction. The relevance of research and development of methods for modeling technological processes in order to increase the efficiency of the use of construction technologies is emphasized. A review of existing methods for describing technological processes of building (structure) construction was conducted and the feasibility of researching and developing methods that take into account various structural and technological factors was substantiated. The basic principles of mathematical and physical modeling and the main technological parameters that constitute the object of research are presented. The features of theoretical and experimental research methods are considered. An analysis of existing methods for describing technological processes (graphs, cyclograms, communication graphs, etc.) was conducted, and their advantages and disadvantages were highlighted. A structural N-dimensional constructive and technological model of the building (structure) construction process is proposed, which combines constructive solutions of the building, engineering systems, and optimization of technological solutions in the general organizational structure of construction. Attention is focused on the fact that the choice of technological solutions in the context of the construction of a building (structure) is based on the understanding of the fact that it is necessary to consider the construction process as a complex model of the interaction of different types of systems, each of which has a set of parameters that change in time and space. In the proposed structural and technological model, the developed structural numerical 3D model of the building, engineering and geological, technological conditions and limitations, as well as conditions regarding engineering systems and communications serve as the initial data. Technological factors in the calculation model (process organization algorithm; human resources; mechanization tools; algorithm for dividing the work front into sections, areas, etc.) are presented in the form of n-dimensional matrices. The proposed structural scheme for constructing an N-dimensional model will allow taking into account the variable technological parameters of the building construction process, the search for optimal solutions, the integration of technological solutions into modern software, as well as the possibility of creating a basis for the use of robotic systems and complexes.